Supplementary Reading Materials for Madrasah Learners based on Genre Approach - Riswanto Riswanto (Jurnal Pendidikan Islam, 2016)
This paper investigated analysis of supplementary reading material development using a genre-based approach which is in line with the school curriculum. It employed the procedures: need analysis, supplementary materials development, expert validation, material revision, material testing, and subsequent material revision. The data were collected by using questionnaires, interview, syllabus analysis, and field note. The analysis shows that the supplementary reading materials entitled Reading for Islamic Learners were completely developed. The supplementary reading materials were developed on student’s need and school recommendation, in line with standard competence and basic competence from syllabus. They contain interesting reading passages featuring Islamic messages, delivered through colorful pictures. In addition they have various reading strategies and accompanied by  evaluation tools covering: multiple choice and essay.